Experimental and numerical investigation on the mechanical performance of novel composite revetment piles - Bixing Yan; Heng Zhang; Hai Fang; Xinchen Zhang; Guolong Xia (Case Studies in Construction Materials)
A novel type of composite revetment pile was investigated. The revetment pile was manufactured using short-cut fibers and PVC plastic through extrusion molding and had currently been applied to revetment projects for medium and small rivers. In this study, three-point bending and four-point bending tests were conducted on a single pile, and a three-point bending test was performed on a combination of two piles. The shear performance and flexural performance of this novel composite revetment pile were investigated. Subsequently, finite element numerical simulation was utilized to analyze the mechanical performance and forces acting on the revetment pile. The results indicated that the ultimate shear capacity of the novel revetment piles was 13.17 kN, with an ultimate bending moment of 5.06 kN∙m. Additionally, the ultimate shear capacity at the splicing point was 2.50 kN, and the component exhibits a certain degree of brittleness. Based on the finite element simulation results, it is recommended to implement anti-tension and pull-out anchoring measures at the top of the revetment pile in practical applications to prevent large displacements when the pile is subjected to stress.